MTUN Academic Colloquium on higher value TVET - Nur Sa’adatul Afzan, Jusoh (2019)
Universiti Malaysia Pahang (UMP) recently organised the Malaysia Technical University Network (MTUN) Academic Colloquium as part of the efforts to further enrich the eco-system of Technical and Vocational Education Training (TVET).